Speaking the truth in Christ: an exegetico-theological study of Galatians 4,12-20 and Ephesians 4,12-16 - Tantiono, Paulus Toni (Tesi gregoriana / Serie teologia, 2008)
The apostle Paul tells his churches the truth of the Gospel (cf. Gal 2,5.14; 4,16): the believer is justified by faith in Christ rather than by the works of the law. The present work is an exegetico-theological study of Galatians 4,12-20 and Ephesians 4,12-16. This study of these two passages shows how important and relevant it has been to speak the truth of the Gospel ever since the very first days of Paul's evangelisation in the early church up until the present, whether the particular circumstances be those of first century Asia Minor or 21st century Indonesia. The most effective way to announce that truth is in love (cf. Gal 5, 13; 6,2; Eph 4, 15-16), the love that comes to Christians from the holy spirit (cf. Gal 5,22; Eph 5, 2.18).